TAX AVOIDANCE: AN AGENCY THEORY PERSPECTIVE - Luthfiatun Niswah; Afrizal Nilwan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Tax Avoidance, or often known as tax avoidance, is an obstacle that has the potential to affect state cash revenue. This arises from the irresponsible behavior of corporate taxpayers who do not fulfill their obligations in paying their taxes, in practice often taking advantage of weaknesses or loopholes in tax regulations. The purpose of this research is to test the impact of transfer pricing, sales growth, capital intensity, and debt to equity ratio on tax avoidance in the oil, gas and coal mining industry listed on the IDX in 2019 – 2022. The method used in sampling is the purposive sampling method through a sample that has a total of 8 out of 19 oil, gas and coal mining industries in the IDX in 2019 – 2022. The variables used in this research are dependent (y) and independent (x) variables. The data analysis used in this research is multiple linear regression using the SPSS version 18 test tool. Based on the results of the analysis carried out, the researchers were able to draw conclusions that the variables transfer pricing, sales growth, capital intensity, and debt to equity ratio had a significant positive effect on tax avoidance, on the significance value of each independent variable (x), namely 0.001, 0.003, 0.042, and 0.010 where the value was smaller than 0.05.